Quality of care indicators for schizophrenia: determinants of observed variations among Italian Departments of Mental Health. Results from the ETAS DSM study. (28th March 2016) - Fantini, G.; Tibaldi, G.; Rucci, P.; Gibertoni, D.; Vezzoli, M.; Cifarelli, L.; Tiraferri, R.; Munizza, C.
Abstract : Aims: The primary aim of this study is to analyse the conformance of usual care patterns for persons with schizophrenia to treatment guidelines in three Italian Departments of Mental Health (DMHs). The secondary aim is to examine possible organisational and structural reasons accounting for variations among DMHs. Methods: Within the framework of the Evaluation of Treatment Appropriateness in Schizophrenia (ETAS) project, 20 consensus quality of care indicators were developed. Ten concerned pharmacological treatment and ten encompassed general care and psychosocial rehabilitation interventions. Indicators were calculated using data from a stratified random sample of 458 patients treated at three DMHs located in North-Eastern, North-Western and Southern Italy. Patients' data were collected by combining information from medical charts and from a survey carried out by the health care professionals in charge of the patients. Data on the structural and organisational characteristics of the DMHs were retrieved from administrative databases. For each indicator, the number and percentage of appropriate interventions with and without moderators were calculated. Appropriateness was defined as the percentage of eligible patients receiving an intervention conformant with guidelines. Moderators, i.e., reasons justifying a discrepancy between the interventions actually provided and that recommended by guidelines were recorded. Indicators based on a sufficient number of eligible patients were further explored in a statistical analysis to compare the performance of the DMHs. Results: In the overall sample, the percentage of inappropriate interventions ranged from 11.1 to 59.3% for non-pharmacological interventions and from 5.9 to 66.8% for pharmacological interventions. Comparisons among DMHs revealed significant variability in appropriateness for the indicators 'prevention and monitoring of metabolic effects', 'psychiatric visits', 'psychosocial rehabilitation', 'family involvement' and 'work'. After adjusting the patient's gender, age and functioning, only the indicators 'Prevention and monitoring of metabolic effects', 'psychiatric visits' and 'work' continued to differ significantly among DMHs. The percentage of patients receiving appropriate integrated care (at least one appropriate non-pharmacological intervention and one pharmacological intervention) was significantly different among the three DMHs and lower than expected. Conclusions: Our results underscore discrepancies among Italian DMHs in indicators that explore key aspects of care of patients with schizophrenia. The use of quality indicators and improved guideline adherence can address suboptimal clinical outcomes, and has the potential to reduce practice variations and narrow the gap between optimal and routine care.